Challenges and Opportunities for Small and Medium Enterprises in Eastern Indonesia in Facing the COVID-19 Pandemic and the New Normal Era - Andri Irawan (TIJAB (The International Journal of Applied Business), 2020)
Eastern Indonesia is one of the areas affected by COVID-19 pandemic. Small and Medium Enterprises (SMEs) such as; culinary businesses are the business sector most affected by this pandemic, where the implementation of social restrictions has resulted in decreased income and also changes in business patterns. This condition certainly provides new challenges and opportunities for SMEs owners. The purpose of this study is to explore the challenges and opportunities of SMEs in eastern Indonesia during the COVID-19 pandemic and the new normal era. The study uses a qualitative approach with an exploratory strategy. The results of the study found that to face the new normal era, SMEs have challenges such as the ability of human resources, understanding of information technology, and business model transformation. An interesting finding in this study is that in facing the new normal era, information technology is not a determining factor for increasing consumer trust and increasing income, but product hygiene and environmental sanitation are the determining factors for the existence of SMEs in eastern Indonesia.